Direct selective laser sintering of hexagonal barium titanate ceramics. Issue 3 (20th November 2020) - Zhang, Xiang; Wang, Fei; Wu, Zhipeng; Lu, Yongfeng; Yan, Xueliang; Nastasi, Michael; Chen, Yan; Hao, Yifei; Hong, Xia; Cui, Bai
Abstract: A direct selective laser sintering (SLS) process was combined with a laser preheating procedure to decrease the temperature gradient and thermal stress, which was demonstrated as a promising approach for additive manufacturing of BaTiO3 ceramics. The phase compositions in BaTiO3 ceramics fabricated by SLS were investigated by X‐ray and neutron diffractions. The surface morphologies and cross‐section microstructures were characterized by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). A dense hexagonal h‐BaTiO3 layer was formed on the surface and extended to a depth of 500 μm, with a relative density higher than 97% and absence of pores or microcracks. SLS resulted in the formation of the high‐temperature phase, h‐BaTiO3, which was retained at room temperature possibly due to the high cooling rate. The grain boundaries of SLSed h‐BaTiO3 ceramics consist of a Ti‐rich secondary phase. Compared with that of the pressureless sintered t‐BaTiO3 ceramics, the Vickers hardness of SLSed h‐BaTiO3 is 70% higher.